2001
DOI: 10.1046/j.0953-816x.2001.01625.x
|View full text |Cite
|
Sign up to set email alerts
|

Fos imaging reveals differential neuronal activation of areas of rat temporal cortex by novel and familiar sounds

Abstract: Fos imaging reveals differential neuronal activation of areas of rat temporal cortex by novel and familiar sounds Article (Published Version) http://sro.sussex.ac.uk Copyright and reuse:Sussex Research Online is a digital repository of the research output of the University.Copyright and all moral rights to the version of the paper presented here belong to the individual author(s) and/or other copyright owners. To the extent reasonable and practicable, the material made available in SRO has been checked for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 42 publications
4
39
2
Order By: Relevance
“…This concept is in line with previous results showing that the Te2 is not significantly activated by non-associative auditory processes, such as long-term habituation to neutral sounds (Gonzalez-Lima and Scheich 1985;Gonzales-Lima et al 1989) and that lesions in the higher order sensory cortices did not destroy the long-term ability to recognize the physical features of the perceived stimuli (Sacco and Sacchetti 2010). Accordingly, novel and familiar sounds activate Te2 neurons in a similar manner in the absence of conditioning (Sacco and Sacchetti 2010;Wan et al 2001), while neural activity in this area increases significantly if the sounds had previously acquired a behavioral value (Cambiaghi et al 2016;Carretta et al 1999;Kwon et al 2012;Grosso et al 2015b;Sacco and Sacchetti 2010). Similar results were reported by Bao et al (Bao et al 2001), who showed that, after pairing of auditory stimuli presentation to ventral tegmental area stimulation, "strong, sharply tuned responses to the paired tones also emerge in a second cortical area [Te2], whereas the same stimuli only evoke 23 poor or non-selective responses in this second cortical field in naive animals."…”
Section: Te2 Participation In Emotional Remote Memorysupporting
confidence: 79%
“…This concept is in line with previous results showing that the Te2 is not significantly activated by non-associative auditory processes, such as long-term habituation to neutral sounds (Gonzalez-Lima and Scheich 1985;Gonzales-Lima et al 1989) and that lesions in the higher order sensory cortices did not destroy the long-term ability to recognize the physical features of the perceived stimuli (Sacco and Sacchetti 2010). Accordingly, novel and familiar sounds activate Te2 neurons in a similar manner in the absence of conditioning (Sacco and Sacchetti 2010;Wan et al 2001), while neural activity in this area increases significantly if the sounds had previously acquired a behavioral value (Cambiaghi et al 2016;Carretta et al 1999;Kwon et al 2012;Grosso et al 2015b;Sacco and Sacchetti 2010). Similar results were reported by Bao et al (Bao et al 2001), who showed that, after pairing of auditory stimuli presentation to ventral tegmental area stimulation, "strong, sharply tuned responses to the paired tones also emerge in a second cortical area [Te2], whereas the same stimuli only evoke 23 poor or non-selective responses in this second cortical field in naive animals."…”
Section: Te2 Participation In Emotional Remote Memorysupporting
confidence: 79%
“…In contrast, the results support the notion of separate, parallel mechanisms outside the perirhinal cortex to support tactile and olfactory recognition memory (see also Winters and Reid 2010). To this list can be added audition, as other animal studies indicate that auditory recognition memory does not depend on the perirhinal cortex Wan et al 2001;Fritz et al 2005). The Parallel Model (Fig.…”
Section: Discussioncontrasting
confidence: 49%
“…An alternative, Parallel Model (Fig. 1B), holds that recognition memory for modalities other than vision relies on separate sensory-specific processes outside the perirhinal region Wan et al 2001;Fritz et al 2005;Winters and Reid 2010). This second model would, however, need to accommodate evidence that the perirhinal region can integrate object information from different senses (Goulet and Murray 2001;Holdstock et al 2009;Winters and Reid 2010).…”
mentioning
confidence: 99%
“…In comparison to visual and olfactory recognition memory, there is less evidence to suggest that it plays a role in auditory recognition memory; the perirhinal cortex showed no significant changes in c-Fos expression following an auditory recognition task (Wan et al, 2001) and a similar study in dogs reinforces this finding . However, the door on the perirhinal cortex's role in auditory recognition is not fully closed.…”
Section: Object Recognition Memorymentioning
confidence: 86%
“…3a; Swanson and Cowan, 1977;Wyss, 1981;Kosel et al, 1982Kosel et al, , 1983Deacon et al, 1983;Kö hler, 1988;Van Groen and Wyss, 1990;Insausti et al, 1997;Burwell and Amaral, 1998a,b;Shi and Cassell, 1999;Kloosterman et al, 2003b). Based on anatomical (Witter et al, 2000b;Witter, 2002), electrophysiological (Young et al, 1997;Ivanco and Racine, 2000;Naber et al, 1997Naber et al, , 1999Naber et al, , 2001a and functional evidence (Bussey et al, 2000;Wan et al, 2001;Burwell et al, 2004a,b;Jenkins et al, 2004;Amin et al, 2006;Albasser et al, 2010;Romero-Granados et al, 2010), the hippocampal-parahippocampal region of the brain has been implicated in several aspects of learning and memory. The role of the perirhinal cortex in this hippocampal-parahippocampal network has been traditionally seen as a gateway for sensory information into the hippocampus via the entorhinal cortex (Witter et al, 2000a,b) but, as discussed below, the current evidence does not fully support this model but points to a more complex relationship between the hippocampal-parahippocampal regions.…”
Section: Hippocampal and Parahippocampal Projectionsmentioning
confidence: 99%